Management Structural Reviewer Of Performance Efficiency By Head Of Administration Officer Of Islamic Senior High School In Lampung Province - Gidayani; Idham Kholid; Meriyati; Septuri; Siti Patimah; Koderi (CV. Inara, 2021)
The performance in question according that Wirawan is oriented to the outcome of a goodwork done by workers who are based on certain skills (profession) and work without beingbased on the work with expertise.The purpose of the research in this journal is to know thework of the administrative officer in the MAN of Lampung province.The results of this studyindicate that (a) the Planning of administrative performance in the Financial AdministrationService has been in accordance with the mechanism in arrange the planning performancemanagement, (b) the communication of the performance of the administration in the FinancialAdministration service has a managerial competence with its style so that it can improve theperformance of the administrative staff who serve the financial administration, (c) evaluationof the performance of administration in the financial administrative services to the supervisionto evaluate the quality of work of the administration in the financial services to the head ofadministration, (d) the development of the performance of the administration in the financialservices conducted through the motivation to improve knowledge through formal educationand training held by the Ministry of Religious Affairs. Head of administration of MANLampung Province has shown good work in providing services, however not yet 100% butapproximately 90% already working provide good service for the satisfaction of teachers,students or interested parties. For example, work on assignments and requests according towhat is commanded. Administrative officers have many ways that can be done in improvingperformance, especially in providing services such as improving existing skills by providingand involving employees in all forms of training. Constraints faced at the time of providingservices, lack of the responsiveness of employees in understanding the psychology ofconsumers, the number of workloads that run with a little short time and the slow response thatis shown by consumers when the administration officers explain what they need